Working relationally with shy students: Pedagogical insights from teachers and students. (April 2022) - Nyborg, Geir; Mjelve, Liv Heidi; Edwards, Anne; Crozier, W. Ray; Coplan, Robert J.
Abstract: Shy children can find engaging with classroom demands challenging, inhibiting their development as agentic learners. In the present study, seven Norwegian elementary school teachers with acknowledged success with shy students were observed teaching and then interviewed about their observed pedagogies. A shy child in each class was also interviewed. Both sets of interviews were analysed drawing on concepts from cultural-historical theory: relational expertise, common knowledge and relational agency. Analyses revealed that teachers employed relational expertise to build common knowledge (understandings of their and the child's motive orientations) with each student. Common knowledge then mediated the unfolding of the child's agency as an engaged learner. The study offers unique insights into how shy children can be supported as learners.